A century of latin-american thought. - Crawford, William Rex, 1898- (Cambridge, Mass : Harvard University Press, 1944)
"The book is aimed especially at North American readers with a medium educational level. The book is an anthology for the study of Latin American thought, so through its pages the reader will meet the patriots and men who are considered great representatives of the culture of Latin America. Also, the author reflects in the text, the attempt to reach the facts of Mexican history." (Carmen Alicia Uriarte Morataya, Biblioteca Central).
Chapter I. Introduction. Chapter II. Independence and Nationhood. Chapter III. The Generation of' 42 and After. Chapter IV. A Reaction - Rodó. Chapter V. Positivism and Idealism in Argentina. Chapter VI. Rebellion on the West Coast. Chapter VII. Trhee Thinkers of Brazil. Chapter VIII. The Cubans and Hostos. Chapter IX. The Mexicans. Chapter X. Conclusion. Bibliography.
Bibliography: p. 299-311
Keywords: LATIN AMERICAN -- INTELLECTUAL LIFE; LATIN AMERICAN -- CIVILIZATION; LATIN AMERICAN -- PHILOSOPHY; AMÉRICA LATINA -- VIDA INTELECTUAL; AMÉRICA LATINA -- CIVILIZACIÓN; FILOSOFÍA LATINOAMERICANA